Pembesaran Ikan Lele Mutiara (Clarias gariepinus) dan Lele Sangkuriang (Clarias batrachus) di Balai Benih Ikan Lokal (BBI) Kota Pontianak, Provinsi Kalimantan Barat - Muslimah Muslimah; Yusri Ramadeni (PAKIS JOURNAL INSTITUTE, 2023)
Catfish is the most commonly cultivated freshwater fishery commodity found in almost all regions of Indonesia. Due to the ease of cultivation and the price, which is quite affordable, Catfish have a fast growth rate and can live in waters with poor conditions. Mutiara catfish and sangkuriang catfish are strains of catfish that are commonly cultivated. So the aim of this research is to observe the rearing and cultivation of pearl catfish and sangkuriang. The rearing activities in this research included preparing containers and water. Seed distribution, feeding, water quality management, growth management, and harvesting In this study, the number of seeds stocked was 200 each for these two types of fish strains. The amount of feed given is also the same, namely 5% of the total biomass. The results of the research showed that the weight growth of mutiara catfish was higher than that of sangkuriang catfish. The final weight of mutiara catfish was 32.38–181.45 grams, and that of sangkuriang catfish was 47.9–111.38 grams. With a survival rate reaching 77% for mutiara catfish and 86% for sangkuriang catfish.